Pengembangan Literasi Numerasi Berbantuan Aplikasi Etnomatematik Puzzle Game pada Pembelajaran Matematika di Sekolah Perbatasan - Niken Eka Priyani (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
Learning mathematics is considered difficult by students of Sekolah Dasar Negeri 29 Idai, so it needs to be a concern for teachers, especially now that numeracy literacy has become a benchmark for the success of the minimum competency assessment (AKM), where students must prepare themselves to take part in the AKM process. This study aims to develop an Ethnomatematical Puzzle Game learning application, namely to improve numeracy literacy results through the use of the Ethnomathematics Puzzle Game application. The research and development (R&D) method used is the Hannafin & Peck model with three stages, namely; 1) needs assessment; 2) design stage; and 3) development and evaluation. Based on the results of media experts and peer reviews, it is known that the media is categorized as feasible and can be used for learning, and the test results show that 84.64% of students are complete in learning. So it can be concluded that the application of ethno mathematical puzzle games can help understanding and improve students' numeracy literacy in mathematics subjects.